Zoonotic surveillance for rickettsiae in rodents and mapping of vectors of rickettsial diseases in India: A multi-centric study - Rina Tilak; Rajesh Kunwar; P K Tyagi; Anurag Khera; R K Joshi; Urmila B Wankhade (Indian Journal of Public Health, 2017)
Background: The global resurgence of rickettsial diseases and their potential to impact the fitness of military personnel and inflict widespread casualties amongst civil populations has emerged as a major cause of public health concern. Absence of surveillance system, lack of awareness amongst medical fraternity to rickettsial activity along with the difficulty in diagnosis because of their protean clinical manifestations are reasons for the outbreaks of these diseases. Objectives: To determine rickettsial activity amongst rodents and study vector diversity, abundance and their distribution to enable mapping of rickettsial hotspots. Methods: Zoonotic surveillance was undertaken in six selected study areas in India - Jammu, Akhnoor, Rajouri-Poonch, Udhampur-Nagrota, Dehradun and Pune. Weil–Felix test was used for rickettsial sero-surveillance amongst rodents and standard identification keys were used for mapping vector diversity and database preparation. Results: Serological findings revealed positivity to all the three rickettsial antigens (OXK, OX19 and OX2) in Jammu, OX19 in Dehradun and OXK and OX2 positivity in Udhampur-Nagrota belt. The vector database records presence of 16 species of trombiculid mites from three important genera - Leptotrombidium, Schoengastiella and Gahrliepia with ticks from five genera and 8 species of fleas from four genera. Mite fauna of study sites has been enriched with addition of new records of mite species (five mite species at Pune, two at Akhnoor with one mite species each at Jammu and Dehradun). Conclusion: The study reveals rickettsial activity amongst rodents at Jammu, Dehradun and Udhampur-Nagrota belt. The results correlate well with the presence of vectors of scrub and tick typhus and corroborate the occurrence of outbreaks of these diseases in the respective areas.